Estudos de viabilidade das redes de distribuição secundárias compactas no sistema elétrico da CELG D - GOMES, Hélio Júnio (2010)
Secondary networks are essential for the process of distributing electrical energy to the final consumer, and their performance is related to their design, the quality of materials and equipment employed, environmental conditions, damage caused by third parties, and maintenance services. In this context, the objective of the present work is to carry out feasibility studies of the compact secondary networks in the distribution system of CELG D, an electric power distribution concessionaire and a crucial element of the electrical system of the state of Goiás, Brazil. The development of this research took into consideration the initial investment, the operational cost and the performance of these networks. It can therefore be concluded that, although the cost of implementation of the compact network is approximately 14% higher than the conventional cost, its installation is extremely viable because, in addition to reducing the preventive maintenance services required for this network, there is an improvement in the continuity of electrical power supply, two factors that are fundamental in an increasingly competitive market.